Exploring the mechanism of Zishen Quyu Jiedu formula in treating endometriosis based on network pharmacology and experimental verification - Wang, Ruolin; Tian, Xinyang; Liu, Peiyu; Lian, Fang (Frontiers in Endocrinology, 2025)
ObjectiveZishen Quyu Jiedu formula (ZQYJDF) is a commonly used prescription for endometriosis (EMs) with clinical efficacy. However, its active components and potential mechanisms remain unknown. This study aimed to identify the key targets and signaling pathways involved in the treatment of EMs by ZSQYJDF and to clarify its mechanism.Materials and methodsMultiple databases were integrated to screen the effective components of ZSQYJDF and their protein targets, with redundancies removed. EMs-related genes were obtained from several disease databases. A drug–component–target network was constructed using overlapping targets. Gene Ontology (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analyses were performed to identify key pathways and proteins. An autologous transplantation rat model of EMs was established. Hematoxylin and eosin (H&E) staining was used to observe lesion morphology; immunohistochemistry (IHC) was used to assess positive expression of NRF2, HO1, and NQO1; serum SOD, MDA, GSHPx, 8epiPGF2α, IL6, IL1β, and TNFα were measured by ELISA; and mRNA and protein levels of NRF2, HO1, NQO1, and KEAP1 in endometrial tissue were detected by qPCR and Western blot.Resultscomparisonon of the screened compounds with 1,225 known disease-related targets identified 134 potential targets for ZSQYJDF. GO terms were enriched in response to oxidative stress and cellular responses to oxidative stress. KEGG pathways were enriched in the TNF, NRF2, and HIF signaling pathways. HPLC-QOrbitrap-MS identified and inferred 48 compounds. In in vivo experiments,ZQYJDF reduced inflammatory cell infiltration in ectopic endometrial stroma, leading to local atrophy of lesions, decreased IL-6, IL-1β, TNF-α, 8-epi-PGF2α, and MDA, increased the expression of NRF2, NQO1, and HO1, and decreased KEAP1.ConclusionUtilizing methods including network pharmacology, HPLC-Q-Orbitrap-MS component identification, and animal experiments, the main active components and potential therapeutic targets of ZSQYJDF were identified, and its mechanism of action in treating EMs was preliminarily elucidated, providing a scientific basis for further research on EMs.